2009
DOI: 10.1111/j.1740-8261.2009.01572.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Sonographic Findings Predict the Results of Liver Aspirates in Dogs With Suspected Liver Disease?

Abstract: While abdominal ultrasound and ultrasound-guided fine-needle aspiration cytology are often combined to help determine the type of liver disease in dogs, little is known about the relationship that may exist between the results of these tests. We hypothesized that specific sonographic findings, or combinations of findings, may predict results of liver ultrasound-guided fine-needle aspiration cytology. Hepatic and extrahepatic sonographic findings were recorded prospectively using a standardized form in 70 dogs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 28 publications
(64 reference statements)
4
30
2
2
Order By: Relevance
“…Another study 26 conducted to investigate the association of ultrasonographic features with liver aspirates found associations between the presence of a large hepatic mass, ascites, abnormal hepatic nodes, and splenic lesions with malignant results on cytologic examination. In the full model, the estimated logarithmic odds of a malignant disease via histologic examination was 0.28/cm, which corresponded to a 1.3-to-1 odds of malignancy for each 1-cm increase in size of an FLL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study 26 conducted to investigate the association of ultrasonographic features with liver aspirates found associations between the presence of a large hepatic mass, ascites, abnormal hepatic nodes, and splenic lesions with malignant results on cytologic examination. In the full model, the estimated logarithmic odds of a malignant disease via histologic examination was 0.28/cm, which corresponded to a 1.3-to-1 odds of malignancy for each 1-cm increase in size of an FLL.…”
Section: Discussionmentioning
confidence: 99%
“…9 Ultrasonographic features of lesions attributable to malignant and benign diseases of the liver may overlap. 16 In a more recent study, 26 it was suggested that certain ultrasonographic features may be associated with the cytologic diagnosis of liver lesions. 10 Target lesions, which consist of a focal lesion with a hyperechoic center surrounded by a hypoechoic rim, were originally considered to be strongly associated with malignancy, but they have also been found to be attributable to benign conditions.…”
mentioning
confidence: 99%
“…83,84,85 Primary hepatobiliary tumors are more common than metastatic disease in cats. 83,89,93,99 Yet another study indicates no correlation of hepatocellular carcinoma with a particular echogenicity. Multifocal nodules involving several lobes, and diffuse, coalescing nodules involving all lobes are additional patterns that have been identified.…”
Section: Neoplasiamentioning
confidence: 99%
“…83,86 Primary liver tumors may appear as solitary masses that are confined to one lobe (Figure 9-19). 93 Mast cell tumor (MCT) infiltration into the liver does not seem to have a distinctive ultrasound appearance. Primary hepatic neoplasias are hepatocellular adenoma and carcinoma; bile duct adenoma (cystadenoma) and carcinoma Continued such as nodular hyperplasia, pyogranulomatous hepatitis, chronic active hepatitis, and cirrhosis may also produce target lesions.…”
Section: Neoplasiamentioning
confidence: 99%
See 1 more Smart Citation